2018
DOI: 10.1038/s41588-018-0195-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrative detection and analysis of structural variation in cancer genomes

Abstract: Structural variants (SVs) can contribute to oncogenesis through a variety of mechanisms. Despite their importance, the identification of SVs in cancer genomes remains challenging. Here, we present a framework that integrates optical mapping, high-throughput chromosome conformation capture (Hi-C), and whole-genome sequencing to systematically detect SVs in a variety of normal or cancer samples and cell lines. We identify the unique strengths of each method and demonstrate that only integrative approaches can co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
307
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(338 citation statements)
references
References 74 publications
16
307
0
6
Order By: Relevance
“…9. We confirmed the authenticity of these two translocations by the software hic_breakfinder and Hi-Ctrans [15,16]. The heatmap generated by DLO Hi-C Tool will provide a visual theoretical basis for chromatin translocation calling.…”
Section: Interaction Matrixsupporting
confidence: 58%
“…9. We confirmed the authenticity of these two translocations by the software hic_breakfinder and Hi-Ctrans [15,16]. The heatmap generated by DLO Hi-C Tool will provide a visual theoretical basis for chromatin translocation calling.…”
Section: Interaction Matrixsupporting
confidence: 58%
“…Furthermore, investigation of the impact of neo‐TADs on gene expression revealed that across eight cancer cell lines, the genes within TADs enclosing rearrangements exhibit greater allelic bias compared with the genes located in non‐rearranged TADs. This strongly suggests that at least a part of SV's events lead to gene expression changes . Activation of silent proto‐oncogenes has been shown to appear on deeper level of chromatin structure due to insulated neighborhood boundary loss as well.…”
Section: Impact Of Chromosome Rearrangements On 3d Genome Structure Imentioning
confidence: 99%
“…This strongly suggests that at least a part of SV's events lead to gene expression changes. 58 Activation of silent proto-oncogenes has been shown to appear on deeper level of chromatin structure due to insulated neighborhood boundary loss as well. Enhancers that are normally located outside the neighborhood changed their locations as a consequence of loss of CTCF-cohesinmediated loop and can cause altered expression of oncogenes.…”
Section: The Inner Structure Of Intermingled Chromosomesmentioning
confidence: 99%
“…Previous work in constitutional genetics has linked the pres-ence of inherited non-coding DNA variants, such as CTCF mutations 10 or larger structural variants 11,12 , to human limb malformations through chromatin re-structuring 10 . In cancer, complex somatic genomic rearrangements can create neo-TADs 11,13 or hijack enhancers to activate oncogenes [14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, Hi-C enables unbiased mapping of active (A) and inactive (B) chromatin compartments, TADs, cohesin loops, and enhancer-promoter interactions among the billions of interacting locus pairs in these genome-wide contact maps. In addition, Hi-C has been applied to generate reference-grade de novo assemblies of mammalian scale genomes 25 , identify structural variants in cancer cells 13 , and study DNA replication 26,27 .…”
Section: Introductionmentioning
confidence: 99%